Chitosan Oleate Coated PLGA Nanoparticles as siRNA Drug Delivery System - Dalila Miele; Xin Xia; Laura Catenacci; Milena Sorrenti; Silvia Rossi; Giuseppina Sandri; Franca Ferrari; John J. Rossi; Maria Cristina Bonferoni (MDPI AG, 2021)
Oligonucleotide therapeutics such as miRNAs and siRNAs represent a class of molecules developed to modulate gene expression by interfering with ribonucleic acids (RNAs) and protein synthesis. These molecules are characterized by strong instability and easy degradation due to nuclease enzymes. To avoid these drawbacks and ensure efficient delivery to target cells, viral and non-viral vectors are the two main approaches currently employed. Viral vectors are one of the major vehicles in gene therapy; however, the potent immunogenicity and the insertional mutagenesis is a potential issue for the patient. Non-viral vectors, such as polymeric nanocarriers, provide a safer and more efficient delivery of RNA-interfering molecules. The aim of this work is to employ PLGA core nanoparticles shell-coated with chitosan oleate as siRNA carriers. An siRNA targeted on HIV-1, directed against the viral Tat/Rev transcripts was employed as a model. The ionic interaction between the oligonucleotide's moieties, negatively charged, and the positive surface charges of the chitosan shell was exploited to associate siRNA and nanoparticles. Non-covalent bonds can protect siRNA from nuclease degradation and guarantee a good cell internalization and a fast release of the siRNA into the cytosolic portion, allowing its easy activation.